2010
DOI: 10.1111/j.1365-2141.2009.08037.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose chemo‐radiotherapy for relapsed or refractory Hodgkin lymphoma and the significance of pre‐transplant functional imaging

Abstract: We previously reported that three risk factors (RF): initial remission duration <1 year, active B symptoms, and extranodal disease predict outcome in relapsed or refractory Hodgkin lymphoma (HL). Our goal was to improve event-free survival (EFS) for patients with multiple RF and to determine if response to salvage therapy impacted outcome. We conducted a phase II intent-to-treat study of tailored salvage treatment: patients with 0 or 1 RF received standard-dose ifosfamide, carboplatin, and etoposide (ICE); pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
71
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 38 publications
2
71
0
3
Order By: Relevance
“…4 Finally, we have proposed that chemosensitive disease should be defined by pretransplant 18 fluorodeoxy glucose-positron emission tomography (FDG-PET) status; those patients with a negative scan have a 5-year EFS of 75% compared with 25% for those patients with improvement of CT but with persistent FDG-PET positivity. [4][5][6][7][8] Similar FDG-PET data were recently confirmed by the transplant group from Washington University. 9 The current comprehensive study incorporates non-cross-resistant SLT and individually tailored RT and HDT/ASCT.…”
Section: Introductionsupporting
confidence: 61%
“…4 Finally, we have proposed that chemosensitive disease should be defined by pretransplant 18 fluorodeoxy glucose-positron emission tomography (FDG-PET) status; those patients with a negative scan have a 5-year EFS of 75% compared with 25% for those patients with improvement of CT but with persistent FDG-PET positivity. [4][5][6][7][8] Similar FDG-PET data were recently confirmed by the transplant group from Washington University. 9 The current comprehensive study incorporates non-cross-resistant SLT and individually tailored RT and HDT/ASCT.…”
Section: Introductionsupporting
confidence: 61%
“…We had evaluated all these factors in our analysis. There are only two recent studies with 4100 patients who had FDG-PET before transplant, 15,25 but treatment offered in these studies are purely institutional research based; augmented chemotherapy with or without radiation and tandem transplant. Schot et al 8 reported 101 patients (78 various NHL and 23 HL), 77 of whom underwent HDC ASCT.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reporting 20 or more HL patients in HDC ASCT setting are limited. [7][8][9][10][11][12][13][14][15]25,26 Many studies have combined various non Hodgkin's lymphoma (NHL) and HL together. Most studies analyzed FDG-PET as an individual risk factor rather than integrating it with all other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that findings on positron emission tomography (PET) imaging performed after salvage chemotherapy and before ASCT, are a critical predictor of outcome in patients with relapsed/refractory (R/R) HL [15][16][17][18]. On the basis of these data, it is reasonable to consider patients with a PET-positive scan at transplantation as an unfavorable group to receive further treatment to improve their outcome.…”
Section: Introductionmentioning
confidence: 99%